Polynomials on algebraic manifolds
In this paper, we study polynomials on algebraic subvarieties AC ^N, A=n, nN, in the point of view their polynomial extensions into the enclosing space C ^N. It is important in observing extremal Green function V(z,K) for compact subset KA. , number=2, journal=Carpathian Mathematical Publications, author=Atamuratov, A.A., year=2024, month=Sep., pages=401–406